Identification, sequence analysis, and expression of a Corynebacterium glutamicum gene cluster encoding the three glycolytic enzymes glyceraldehyde-3-phosphate dehydrogenase, 3-phosphoglycerate kinase, and triosephosphate isomerase. - Eikmanns, B J (1992)
To investigate a possible chromosomal clustering of glycolytic enzyme genes in Corynebacterium glutamicum, a 6.4-kb DNA fragment located 5' adjacent to the structural phosphoenolpyruvate carboxylase (PEPCx) gene ppc was isolated. Sequence analysis of the ppc-proximal part of this fragment identified a cluster of three glycolytic genes, namely, the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene gap, the 3-phosphoglycerate kinase (PGK) gene pgk, and the triosephosphate isomerase (TPI) gene tpi. The four genes are organized in the order gap-pgk-tpi-ppc and are separated by 215 bp (gap and pgk), 78 bp (pgk and tpi), and 185 bp (tpi and ppc). The predicted gene product of gap consists of 336 amino acids (M(r) of 36,204), that of pgk consists of 403 amino acids (M(r) of 42,654), and that of tpi consists of 259 amino acids (M(r) of 27,198). The amino acid sequences of the three enzymes show up to 62% (GAPDH), 48% (PGK), and 44% (TPI) identity in comparison with respective enzymes from other organisms. The gap, pgk, tpi, and ppc genes were cloned into the C. glutamicum-Escherichia coli shuttle vector pEK0 and introduced into C. glutamicum. Relative to the wild type, the recombinant strains showed up to 20-fold-higher specific activities of the respective enzymes. On the basis of codon usage analysis of gap, pgk, tpi, and previously sequenced genes from C. glutamicum, a codon preference profile for this organism which differs significantly from those of E. coli and Bacillus subtilis is presented.